Sex Influence On the Temporal Evolution of the Lipid Profile in Patients with Ischemic Heart Disease Participating in a Cardiac Rehabilitation Program (Revista de Medicina Clinica, 2025)
Introduction: This study evaluates the influence of sex on the clinical and epidemiological characteristics of patients participating in a contemporary Cardiac Rehabilitation Program (CRP). It examines the impact of new scientific recommendations and pharmacological treatment on lipid profiles. Patients and Methods: A prospective, single-center study was conducted on patients with ischemic heart disease enrolled in a CRP (2015–2020). Demographic, clinical, and lipid profile data were collected at four time points. The evolution of low-density lipoprotein cholesterol (LDL-C) was analyzed by sex, and temporal cohorts were compared pre- and post-implementation of the 2019 European guidelines for dyslipidemia management. Results: A total of 1,379 patients were included (83% male, mean age 61.5±11 years). The most prevalent cardiovascular risk factors were dyslipidemia (66.8%), hypertension (53.5%), diabetes mellitus (32.4%), and smoking (37.4%). LDL-C levels significantly decreased during the CRP, with lower baseline values in men than in women (66.4 mg/dL ±21.6 vs. 70.5 mg/dL ±23.2, p
Keywords: Cardiac rehabilitation; Lipid profile; Ischaemic heart disease; Secondary prevention